Bentuk-bentuk Petulangan Dalam Upacara Ngaben Ditinjau Dari Sudut Kesenirupaan Di Bali - I Dewa Made Pastika (Mudra Jurnal Seni Budaya, 2008)
The Art of sarcophagus has been known in Bali since ancient up to now in relationship with a cremation ceremony called “ Ngaben” or “ Pelebon”. Its function is as a plase for the dead body during cremation in order that the dead body is protected and its ash can be easily collected after the cremation Phylosophically, sarco- phagi whith are shape of animals have. a meaning of a pach into the heaven for the soul of the cremated body. Besides, if we view them from the art aspect, they hava special artistic velues and special beauty which become an important cultural asset to attract tourist who want to watch them. Ornaments of the sarcophagi generally used in Bali, are taken from animals such as lion, deer, akin of dragon, gedarba, tiger, and kinds of fish. The shaped sarcophagi are adorned with carved ornaments or with cutouts which are stuck on them and made from paper with various carving motif and coloured-catton thread for example: takep pala, takep piah, pengampad, badong, bottems cover ornament, fire tongue, “ gunala”, “karang guak”, “dure “. Ornaments carved in va- rious motif such as “patra punggel”, “patra sari”, mas-masan, “cra- cap”, patra cina “ and other “ kekarangan “. Comparison elements have important role on the beauty of sarcophagus work such as the comparison between the height and the length of the sarcophagus. Sarcophagi not only have special religious meaning, but olso they have high artistic value which should be developed in the future.